Conditional Alpl Ablation Phenocopies Dental Defects of Hypophosphatasia. (January 2017) - Foster, B.L.; Kuss, P.; Yadav, M.C.; Kolli, T.N.; Narisawa, S.; Lukashova, L.; Cory, E.; Sah, R.L.; Somerman, M.J.; Millán, J.L.
Loss-of-function mutations in ALPL result in hypophosphatasia (HPP), an inborn error of metabolism that causes defective skeletal and dental mineralization. ALPL encodes tissue-nonspecific alkaline phosphatase, an enzyme expressed in bone, teeth, liver, and kidney that hydrolyzes the mineralization inhibitor inorganic pyrophosphate. As Alpl -null mice die before weaning, we aimed to generate mouse models of late-onset HPP with extended life spans by engineering a floxed Alpl allele, allowing for conditional gene ablation (conditional knockout [cKO]) when crossed with Cre recombinase transgenic mice. The authors hypothesized that targeted deletion of Alpl in osteoblasts and selected dental cells ( Col1a1- cKO) or deletion in chondrocytes, osteoblasts, and craniofacial mesenchyme ( Prx1- cKO) would phenocopy skeletal and dental manifestations of late-onset HPP. Col1a1- cKO and Prx1- cKO mice were viable and fertile, and they did not manifest the epileptic seizures characteristic of the Alpl -/- model of severe infantile HPP. Both cKO models featured normal postnatal body weight but significant reduction as compared with wild type mice by 8 to 12 wk. Plasma alkaline phosphatase for both cKO models at 24 wk was reduced by approximately 75% as compared with controls. Radiography revealed profound skeletal defects in cKO mice, including rachitic changes, hypomineralized long bones, deformations, and signs of fractures. Microcomputed tomography confirmed quantitative differences in cortical and trabecular bone, including decreased cortical thickness and mineral density. Col1a1- cKO mice exhibited classic signs of HPP dentoalveolar disease, including short molar roots with thin dentin, lack of acellular cementum, and osteoid accumulation in alveolar bone. Prx1- cKO mice exhibited the same array of periodontal defects but featured less affected molar dentin. Both cKO models exhibited reduced alveolar bone height and 4-fold increased numbers of osteoclast-like cells versus wild type at 24 wk, consistent with HPP-associated periodontal disease. These novel models of late-onset HPP can inform on long-term skeletal and dental manifestations and will provide essential tools to further studies of etiopathologies and therapeutic interventions.